South-Bauchi West Pronominal and TAM Systems - (:unkn) unknown (My University, 2006)
This study of the SBW pronominal and TAM system is based on personal data collected in Nigeria on 8 languages : Zaranda, Langas, Dir, Danche, Baraza, Dott, Sigidi and Zaar. In their pronominal system, these languages have lost the gender, inclusive/exclusive and dual marks characteristic of AfroAsiatic (AA) languages. They have in common a system that has eroded and realigned to the point that (i) the exponents of persons are the same in the plural and the singular ; (ii) number is expressed by specific elements: a change of tone, a -N suffixed to the pronoun or addition of a suffix to the verb. It should be noted that the AA feminine mark *t- has become the general common mark for the 3s pronouns. As far as TAM systems are concerned, Zaar stands out as oddly original : it has three tone levels, when the others have two; it has ten TAM paradigms that can combine, when the others only have between three and five that don't ; it marks aspect, tense and mood, whereas the others don't express time in their verbal system, the future being a clear case of mood subcategorization. These differences have sociolinguistic origins: whereas all the other SBW languages are spoken in no more than one village and its wards, Zaar is spoken in over sixty, close to eighty if we add Sigidi. The Zaars have come to their present situation by incorporating exogeneous populations which are still identified by the clan system : Angas, Boi, Pyem, Jaar, etc. It has resulted in a complexification of the language which goes against the general assumption that when absorbing a large quantity of foreign population, a language goes through a process of pidginization.
Keywords: African Research